Construction of miRNA–mRNA networks for the identification of lung cancer biomarkers in liquid biopsies - Espinosa García, Elena María; Arroyo Varela, Macarena; Larrosa-Jiménez, Rafael; Gómez‑Maldonado, Josefa; Cobo Dols, Manuel Ángel; Claros-Díaz, Manuel Gonzalo; Bautista-Moreno, Rocío (Springer Nature, 2022)
Lung cancer (LC) is the most common cause of cancer death worldwide mostly due to the low survival rate: 75% of cases are identified in advanced stages. In this study, the list of useful biomarkers to make an early diagnosis using liquid biopsies was expanded. A total of 30 samples of LC were analyzed to define potential miRNA biomarkers in liquid biopsies for LC. The biomarkers have been identified in interaction networks miRNA–mRNA. The potential biomarkers have been then validated in large cohorts. A total of 15 candidate miRNAs, that regulate the repression of 30 mRNAs, have been identified as a specific functional interaction network for squamous carcinoma, while the specific functional interaction network of adenocarcinoma consists of four candidate miRNAs that seem to handle the repression of five mRNA. Inspection of expression levels in larger cohorts validates the usefulness of the 11 candidates as biomarkers in liquid biopsies. The 11 candidate miRNAs found could be utilized to form diagnostic predictive biomarkers for LC in liquid biopsies.
Keywords: Ácido ribonucleico; Cáncer - Investigación; Oncología; High-throughput sequencing; RNA-seq biomarker; miRNA; Lung cancer